Fermentation time effect on the quality of ancestral cocoa cultivars from Upala, Costa Rica, using physicochemical and sensory characteristics - Wexler Goering, Lea Margarita (2025)
Fine-flavor cocoa can lose sensory attributes when fermented without time and temperature control. This study aimed to assess the effect of micro-batch fermentation time on five organic cocoa cultivars from Upala, Costa Rica (three ancestral or “acriollado” due to Criollo origin, one Forastero, and a clone mixture) by physicochemical, volatile compounds, and sensory analysis. Two ancestral cultivars developed key aroma compounds in 120 h, related to tropical fruits, citric, and floral, while the other developed volatiles related to nuts and caramel in 72 h. Reducing cocoa fermentation time using micro batches can significantly contribute to small farmers’ productivity while developing unique aromas. Cultivars from different genetic origins (Forastero and Criollo) grown on the same farm revealed similar characteristics, suggesting hybridization and the region’s climate and soil conditions positive effect. Evaluation of pure cocoa paste may improve the precision of sensory analysis in relation to volatiles.